2007
DOI: 10.1186/bcr1772
|View full text |Cite
|
Sign up to set email alerts
|

A critical evaluation of loss of heterozygosity detected in tumor tissues, blood serum and bone marrow plasma from patients with breast cancer

Abstract: Introduction The aim of the study was to perform a comparative analysis of LOH (loss of heterozygosity) in primary tumors as well as peripheral blood and bone marrow (BM) of patients with breast cancer (BCa).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 39 publications
0
33
0
Order By: Relevance
“…The gene product of this tumor suppressor gene has been involved in a number of cellular processes including DNA repair and recombination, cell-cycle checkpoint control, chromatin remodeling, ubiquitination, and apoptosis (26). Deletions of BRCA1 have recently been implicated in local recurrence and bad prognosis (10,(27)(28)(29). Because repression of BRCA1 may cause increased genomic instability, its loss may contribute to the aggressive features of HER2-positive breast tumors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The gene product of this tumor suppressor gene has been involved in a number of cellular processes including DNA repair and recombination, cell-cycle checkpoint control, chromatin remodeling, ubiquitination, and apoptosis (26). Deletions of BRCA1 have recently been implicated in local recurrence and bad prognosis (10,(27)(28)(29). Because repression of BRCA1 may cause increased genomic instability, its loss may contribute to the aggressive features of HER2-positive breast tumors.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that RB1 gene is inactivated in about 20% of breast carcinomas (39). Genetic aberrations of this region have been described to frequently occur in breast cancer and to associate with tumor progression, poor prognosis (10,40), and especially with the inability of cells to differentiate (39). RB1 acts as a master regulator by interacting and controlling numerous proteins.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,10,11 Another possible confounder is the fact that DNA molecules are relatively stable, and therefore the detection of tumor specific genomic aberrations may not necessarily indicate the presence of intact DTC but also DNA fragments derived from necrotic or apoptotic tumor cells. [40][41][42] Therefore, measurements of epithelium-specific or more organspecific mRNA species such as CK19 and 20 or mammaglobin or PSA mRNA by RT (reverse transcriptase)-PCR have been proven as more promising to detect DTC in BM samples. [43][44][45][46][47][48][49][50] The main advantage of very sensitive RT-based techniques for the detection of DTC at the single-cell level is the nearly ''unlimited'' availability of primers for almost every gene of interest.…”
Section: Molecular Detection Of Dtcmentioning
confidence: 99%